Contact material
By embedding particles formed from specific non-conductive organic compounds in the silver-containing layer of the contact material, the problem of conductive particles falling off due to frequent plugging and unplugging is solved, and a contact material with high wear resistance and conductivity is realized.
Patent Information
- Application Number
- CN202380048898.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-21
AI Technical Summary
During frequent insertion and removal of existing contact materials, conductive particles are prone to fall off, resulting in short circuits in contacts and insufficient wear resistance and conductivity.
A silver-containing layer containing more than 50% silver is used, and particles formed of a specific non-conductive organic compound are embedded in it. By controlling the area of the particles buried in the silver-containing layer, conductivity and wear resistance are ensured.
It effectively inhibits the shedding of conductive particles, prevents contact short circuits, and improves the wear resistance and conductivity of the material.
Smart Images

Figure CN119343483A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to contact materials. Background Art
[0002] As CO2 emission regulations are tightened, it is expected that electric vehicles (EVs) and plug-in hybrid electric vehicles (PHEVs) with low dependence on fossil fuels will increase. Because these cars need to charge their batteries on a daily basis, the number of plugging and unplugging of the contact materials connecting the external power supply to the car will increase significantly compared to the contact materials of existing cars. Automobile contact materials generally use silver (Ag) plating with high conductivity (low contact resistance), but in general, Ag plating has low hardness and is prone to "sticking" when Ag slides on each other. As a result, the Ag plating is easily worn out during repeated plugging and unplugging (sliding).
[0003] The following studies have been conducted to improve the wear resistance of Ag coatings:
[0004] (1) High hardness of Ag plating achieved by grain refinement
[0005] (2) High hardness achieved by alloying Ag with Se (selenium) or Sb (antimony).
[0006] However, even by any of the above methods (1) and (2), the improvement of wear resistance is still insufficient. In addition, Se and Sb are toxic elements, and not only do they require care in management, but they also cause a problem of reduced conductivity due to alloying.
[0007] In addition, the improvement of wear resistance other than the high hardness of the Ag plating film has also been studied, mainly as disclosed in Non-Patent Documents 1 and 2, and the following research has been conducted:
[0008] (3) Eutectoid deposition of carbon particles into the Ag coating (dispersion plating).
[0009] In these studies, graphite, carbon black (CB) or carbon nanotubes (CNT) are mainly used. The reasons are as follows: (i) carbon particles such as graphite act as solid lubricants, which can be expected to improve wear resistance; and (ii) carbon particles are conductive, so when they are eutectic (dispersed) in the Ag plating film, there is little possibility of deteriorating the contact resistance. In fact, Non-Patent Document 1 discloses an Ag-graphite composite plating film obtained by suspending graphite particles in an Ag plating solution and plating them, which can achieve good wear resistance not only compared with Ag plating, but also compared with hard Ag-Sb alloy plating.
[0010] Prior art literature
[0011] Non-patent literature
[0012] Non-patent document 1: Materials, Vol. 58, No. 1 (2019), p41-43
[0013] Non-patent document 2: Surface Technology Association, 81st Lecture Conference Abstracts, 27A-1 Summary of the invention
[0014] Problems to be solved by the invention
[0015] Regarding the above (3), as shown in non-patent document 2, long-term research has been conducted, and it can be said that it is generally used as a method to improve the wear resistance of silver-containing films. However, with the forecast increase in EVs and PHEVs, despite the rising demand for contact materials that have both wear resistance and conductivity, there has been no progress in the effective use of the above (3). The reason for this is believed to be due to the following concerns. If carbon particles are dispersed and plated on contact materials and repeatedly slide (plug and unplug), the carbon particles retained in the Ag plating film will fall off due to wear. If carbon particles fall off and accumulate around the contacts, it may cause a short circuit of the contacts, especially in terminals for EVs and PHEVs that require power supply at high voltages and large currents, which will cause safety problems.
[0016] The present invention has been made in view of the above circumstances, and one object of the present invention is to provide a contact material that can sufficiently suppress short circuits of contacts due to the falling of conductive particles and has sufficient wear resistance and conductivity.
[0017] Means of solving the problem
[0018] A first aspect of the present invention is a contact material comprising a silver-containing film, wherein:
[0019] The silver-containing film comprises: a silver-containing layer containing 50% by mass or more of silver; a plurality of particles formed of a non-conductive organic compound, at least a portion of each particle being buried in the silver-containing layer,
[0020] The non-conductive organic compound contains in the unit molecular structure: fluorine group (-F), methyl group (-CH3), carbonyl group (-C (=O)-), amino group (-NR 1 R 2 , where R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2 may be the same or different), any one or more selected from the group consisting of a hydroxyl group (-OH), an ether bond (-O-) and an ester bond (-C(=O)-O-),
[0021] The following formula (1) is satisfied.
[0022] 0.50≤A p / (A p +A Ag )×100≤12.10 …(1)
[0023] In formula (1), A p A is the area of the portion of the plurality of particles formed of the non-conductive organic compound buried in the silver-containing layer in a cross section parallel to the film thickness direction of the silver-containing film, Ag It is the area of the silver-containing layer in a cross section parallel to the film thickness direction of the silver-containing film.
[0024] Mode 2 of the present invention is a contact material according to Mode 1, wherein, for the non-conductive organic compound, when a thermogravimetric differential thermal analysis is performed at a heating rate of 10°C / min from room temperature to a maximum of 1000°C, the melting point is above 140°C, or no melting point is shown.
[0025] Mode 3 of the present invention is a contact material according to mode 1 or 2, wherein, for the non-conductive organic compound, when a thermogravimetric differential thermal analysis is performed from room temperature to a maximum of 1000°C at a heating rate of 10°C / min, when a decomposition point is displayed, the decomposition point is below 500°C, and when a melting point is displayed instead of a decomposition point, the melting point is below 500°C.
[0026] A fourth aspect of the present invention is a contact material according to any one of aspects 1 to 3, wherein the non-conductive organic compound contains, in a unit molecular structure, a carbonyl group (-C(=O)-), an amino group (-NR 1 R 2 , where R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2 Any one or more selected from the group consisting of hydroxyl group (-OH).
[0027] Effects of the Invention
[0028] According to the embodiment of the present invention, it is possible to provide a contact material that can sufficiently suppress short circuit of the contact due to the falling of conductive particles and has sufficient wear resistance and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic cross-sectional view of an example of a contact material according to an embodiment of the present invention.
[0030] Figure 2 This is a schematic cross-sectional view of another example of the contact material according to the embodiment of the present invention.
[0031] Figure 3A This is a cross-sectional SEM image of the contact material No. 2 of Example 1, parallel to the film thickness direction of the silver-containing film.
[0032] Figure 3B is from Figure 3A The image is obtained by cutting out only the silver film.
[0033] Figure 3C Yes Figure 3B The binarized image.
[0034] Figure 4 These are the results of evaluating the heat resistance of the contact material No. 10 of Example 2.
[0035] Figure 5 These are the results of evaluating the heat resistance of the contact material No. 11 of Example 2.
[0036] Figure 6 These are the results of evaluating the heat resistance of the contact material No. 12 of Example 2.
[0037] Figure 7 These are the evaluation results of the wear resistance of the contact material No. 13 of the reference example.
[0038] Figure 8 These are the evaluation results of the wear resistance of the contact material No. 14 of the reference example.
[0039] Fig. 9 These are the evaluation results of the wear resistance of the contact material No. 15 of the reference example.
[0040] Fig.10 These are the evaluation results of the wear resistance of the contact material No. 16 of the reference example.
[0041] Fig.11 These are the evaluation results of the wear resistance of the contact material No. 17 of the reference example.
[0042] Fig.12 These are the evaluation results of the wear resistance of the contact material No. 18 of the reference example.
[0043] Fig.13 These are the evaluation results of the wear resistance of the contact material No. 19 of the reference example.
[0044] Fig.14 These are the evaluation results of the wear resistance of the contact material No. 20 of the reference example.
[0045] Fig.15 These are the evaluation results of the wear resistance of the contact material No. 21 of the reference example.
[0046] Fig.16These are the evaluation results of the wear resistance of the contact material No. 22 of the reference example.
[0047] Fig.17 These are the evaluation results of the wear resistance of the contact material No. 23 of the reference example.
[0048] Fig.18 These are the evaluation results of the wear resistance of the contact material No. 24 of the reference example.
[0049] Fig.19 These are the evaluation results of the wear resistance of the contact material No. 25 of the reference example.
[0050] Fig. 20 These are the evaluation results of the wear resistance of the contact material No. 26 of the reference example.
[0051] Fig.21 These are the evaluation results of the wear resistance of the contact material No. 27 of the reference example.
[0052] Fig. 22 These are the evaluation results of the wear resistance of the contact material No. 28 of the reference example. DETAILED DESCRIPTION
[0053] The inventors of the present invention have conducted research from various perspectives to achieve a contact material that can fully suppress contact short circuits caused by the shedding of conductive particles and has sufficient wear resistance and conductivity. In the research of the existing eutectoid plating technology described in non-patent document 1, carbon particles are used as solid lubricating materials (and have good conductivity). However, as a result of the research conducted by the inventors of the present invention, it is found that sufficient wear resistance and conductivity can be obtained by having a silver-containing film in which particles formed of a specific non-conductive organic compound that do not necessarily have a solid lubricating effect are eutected (buried) in a silver-containing layer in a specified amount. This is believed to be because, when the silver-containing film slides, for example, a part of the non-conductive organic compound decomposes and diffuses and moves to the vicinity of the surface of the contact material, and / or a part of the non-conductive organic compound reacts with the silver-containing layer near the surface of the contact material to reduce the friction coefficient near the surface of the contact material, etc., thereby improving the wear resistance of the contact material. Furthermore, since the amount of the decomposition products and the reaction products is small and the ratio of the particles composed of the specific non-conductive organic compound in the silver-containing film is controlled to be below a predetermined value, it is considered that sufficient conductivity can be ensured.
[0054] Based on the above, a contact material can be realized that can sufficiently suppress the risk of contact short circuit caused by the falling of conductive particles and has sufficient wear resistance and conductivity. In addition, the above mechanism does not limit the technical scope of the embodiment of the present invention.
[0055] The following describes in detail each requirement specified in the embodiment of the present invention.
[0056] The contact material of the embodiment of the present invention comprises a silver-containing film, wherein the silver-containing film comprises: a silver-containing layer containing 50% by mass or more of silver; a plurality of particles formed of a non-conductive organic compound, at least a portion of each particle being buried in the silver-containing layer, wherein the non-conductive organic compound comprises, in a unit molecular structure, a fluorine group (-F), a methyl group (-CH3), a carbonyl group (-C(=O)-), an amino group (-NR 1 R 2 , where R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2 The hydroxyl groups may be the same or different), any one or more selected from the group consisting of a hydroxyl group (—OH), an ether bond (—O—), and an ester bond (—C(═O)—O—), and the hydroxyl groups satisfy the following formula (1).
[0057] 0.50≤A p / (A p +A Ag )×100≤12.10 …(1)
[0058] In formula (1), A p A is the area of the portion of the plurality of particles formed of the non-conductive organic compound buried in the silver-containing layer in a cross section parallel to the film thickness direction of the silver-containing film, Ag It is the area of the silver-containing layer in a cross section parallel to the film thickness direction of the silver-containing film.
[0059] According to the above, the risk of contact short circuit due to the falling of the conductive particles can be sufficiently suppressed, and sufficient wear resistance and conductivity can be imparted.
[0060] Figure 1 A schematic cross-sectional view showing an example of a contact material according to an embodiment of the present invention. Figure 1 In the embodiment, the contact material 1 includes a silver-containing film 2, and the silver-containing film 2 includes: a silver-containing layer 2a; and a plurality of particles 2b (hereinafter referred to as "particles 2b") formed of a non-conductive organic compound containing the above-mentioned specific functional groups in a unit molecular structure. In addition, Figure 1 This is a cross section parallel to the film thickness direction of the silver-containing film 2 (and the silver-containing layer 2 a ).
[0061] At least a portion of each particle 2b is buried in the silver-containing layer 2a. In other words, each particle 2b is completely buried in the silver-containing layer 2a, or a portion of each particle 2b is buried in the silver-containing layer 2a, and the remaining portion is exposed from the surface of the silver-containing layer 2a. In addition, the area A of the portion buried in the silver-containing layer 2a among the plurality of particles 2b is controlled in such a manner as to satisfy the above formula (1). p and the area A of the silver-containing layer 2a Ag .
[0062] The silver-containing layer 2a is a layer containing 50% by mass or more of silver. As the silver-containing layer 2a, in addition to soft Ag plating, hard Ag plating, glossy Ag plating, and semi-glossy Ag plating used in the usual terminal surface treatment, alloy plating can also be used for the purpose of improving the corrosion resistance (sulfurization resistance, etc.) and wear resistance of the substrate. However, since the wear resistance is mainly imparted by the particles 2b, when there is no other purpose such as improving corrosion resistance, it is preferred to use a pure Ag plating layer with excellent conductivity, for example, preferably containing 90% by mass or more of silver, more preferably containing 95% by mass or more, and further preferably containing 99% by mass or more.
[0063] The average thickness of the silver-containing layer 2a (for example, the average thickness of the silver-containing layer 2a obtained from any two or more locations of the contact material 1) is not particularly limited and can be appropriately adjusted according to the application, for example, it can be 100 μm or less, and can also be 50 μm or less.
[0064] Regarding the particles 2b, the term "non-conductive" means that they do not exhibit conductivity, and refers to, for example, a volume resistivity of about 10 3 [Ω・cm] or more.
[0065] Regarding the particle 2b, the so-called "organic compound" refers to a compound containing carbon, excluding compounds with simple structures such as carbon monoxide, carbon dioxide, carbonates, hydrocyanic acid, cyanates, thiocyanates, B4C and SiC. For example, silicone resins having a siloxane bond (-Si-O-Si-) as the main chain and an organic group in the side chain are included in the "organic compound" in this specification.
[0066] The non-conductive organic compound constituting the particle 2b includes a fluorine group (-F), a methyl group (-CH3), a carbonyl group (-C(=O)-), an amino group (-NR 1 R 2 , where R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2The non-conductive organic compound constituting the particle 2b preferably contains at least one of a carbonyl group (-C (=O)-), an amino group (-NR) and an ester group (-C (=O)-O-). 1 R 2 , where R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2 Here, the "unit molecular structure" refers to one repeating unit in the case of a macromolecular (polymer) and a single molecule in the case of a non-polymer.
[0067] The non-conductive organic compound constituting the particle 2b preferably has a melting point of 140°C or more, or does not show a melting point (i.e., decomposes without melting). Thus, when the contact material 1 (and the contact material 11 described later) is heated to 140°C, the deterioration of the wear resistance caused by the melting of the organic compound can be suppressed. More preferably, the melting point of the non-conductive organic compound constituting the particle 2b is 160°C or more. Here, the so-called "melting point" is, for example, a melting point obtained by thermogravimetric differential thermal analysis (TG-DTA) from room temperature to a maximum of 1000°C at a heating rate of 10°C / min in the atmosphere. Specifically, the temperature in the temperature range where the mass reduction in the TG curve is less than 1%, and in the DTA curve, as the temperature rises, the temperature of the intersection of the extrapolated line of the straight line to the first inflection point where the heat flow begins to decrease and the extrapolated line after the second inflection point where the heat flow begins to decrease with a certain slope (i.e., the straight line of the fixed slope) can be used as the melting point. In addition, when the non-conductive organic compound constituting the particle 2b does not show a melting point (in the case of such a compound that decomposes without melting), the decomposition point is preferably 140°C or more, more preferably 160°C or more, 200°C or more, 250°C or more, or 300°C or more. Here, the so-called "decomposition point" is, for example, a decomposition point obtained by performing a thermogravimetric differential thermal analysis (TG-DTA) from room temperature to a maximum of 1000°C at a heating rate of 10°C / min in the atmosphere. Specifically, the temperature in the temperature range where a mass reduction of 1% or more is confirmed in the TG curve, and the temperature of the intersection of the extrapolated line of the straight line to the first inflection point where the heat flow begins to decrease as the temperature rises in the DTA curve and the extrapolated line after the second inflection point where the heat flow begins to decrease with a constant slope (i.e., the straight line of the fixed slope) can be used as the decomposition point.
[0068] The non-conductive organic compound constituting the particles 2b preferably has a decomposition point of 500°C or less from the viewpoint of improving the wear resistance of the contact material 1 (and the contact material 11 described later). The decomposition point is more preferably 450°C or less, and further preferably 400°C or less. In addition, when a melting point is shown instead of a decomposition point (a case where such a compound melts but does not decompose), the melting point is preferably 500°C or less, more preferably 450°C or less, and further preferably 400°C or less.
[0069] The combustion point of the non-conductive organic compound constituting the particle 2b is not particularly limited, and may be, for example, 180°C or higher. Here, the "combustion point" is, for example, the combustion point obtained by performing a thermogravimetric differential thermal analysis (TG-DTA) from room temperature to a maximum of 1000°C at a heating rate of 10°C / min in the atmosphere. Specifically, the temperature in the temperature range where a mass reduction of 1% or more is confirmed in the TG curve, and in the DTA curve, as the temperature rises, the temperature of the intersection of the extrapolated line of the straight line up to the first inflection point where the heat flow begins to increase and the extrapolated line after the second inflection point where the heat flow begins to increase with a certain slope (i.e., the straight line of the fixed slope) can be used as the combustion point.
[0070] Regarding the particles 2b, the so-called "particles" means relatively small substances with an equivalent circle diameter of 50 μm or less, and any shape is acceptable. In one embodiment of the present invention, from the viewpoint of conductivity, the average particle size (average equivalent circle diameter) of the particles 2b may be 10 μm or less. In addition, in one embodiment of the present invention, from the viewpoint of wear resistance, the average particle size of the particles 2b may be 0.1 μm or more.
[0071] The area ratio of the above formula (1) [A p / (A p +A Ag )×100 (%)] is 12.10%. This can improve the conductivity. The upper limit is preferably 10.00%. On the other hand, the area ratio [A p / (A p +A Ag )×100(%)] is 0.50%. This can improve wear resistance. The lower limit is preferably 1.50%.
[0072] The area A of the silver-containing layer 2a Ag, can be obtained by binarizing the cross-sectional SEM image parallel to the film thickness direction of the silver-containing film 2 using image processing software (such as "ImageJ"). Specifically, in the cross-sectional SEM image, the silver-containing layer 2a appears brighter (i.e., white), and the protective layer of the cross-sectional SEM sample appears darker (i.e., black). Therefore, for example, the area of the bright portion after binarization using the brightness between the silver-containing layer 2a and the protective layer as a threshold value can be used as the area A of the silver-containing layer 2a. Ag In addition, when the upper surface of the silver-containing layer 2a has irregularities in the cross-sectional SEM image, the average line of the irregularities can be used as the boundary line between the silver-containing layer 2a and the upper layer (e.g., the protective layer of the cross-sectional SEM sample) to calculate the area of the silver-containing layer 2a. The same is true for the lower surface of the silver-containing layer 2a.
[0073] On the other hand, the area A of the portion of the plurality of particles 2b buried in the silver-containing layer 2a is p , which is the dark part (corresponding to the part of the non-conductive organic compound) after the binarization process, can be regarded as the area of the part buried in the silver-containing layer 2a. In addition, when the upper surface of the silver-containing layer 2a has unevenness in the cross-sectional SEM image, the average line of the unevenness is regarded as the boundary line between the silver-containing layer 2a and the upper layer (for example, the protective layer of the cross-sectional SEM sample), and the part existing below the average line is regarded as the part buried in the silver-containing layer 2a. The same applies to the lower surface of the silver-containing layer 2a.
[0074] Figure 2 A schematic cross-sectional view showing another example of the contact material according to the embodiment of the present invention shows that in the contact material 11 , all particles 2 b are buried in the silver-containing layer 2 a . Figure 2 In the case of the above, the particle 2b is of a size that can be completely buried in the silver-containing layer 2a, that is, the average particle size of the particle 2b can be lower than the average thickness of the silver-containing layer 2a. Also, Figure 2 This is a cross section parallel to the film thickness direction of the silver-containing film 2 (and the silver-containing layer 2 a ).
[0075] From the viewpoint of further improving the conductivity (further reducing the contact resistance), it is preferred that Figure 2 In this way, each particle 2b is completely buried in the silver-containing layer 2a. On the other hand, from the viewpoint of further improving the wear resistance, it is preferred to Figure 1 This is a form in which a part of the particles 2b is buried in the silver-containing layer 2a and the rest is exposed from the surface of the silver-containing layer 2a.
[0076] Without departing from the purpose of the embodiment of the present invention, the contact materials 1 and 11 may also contain other particles besides the particles 2b. For example, the contact materials 1 and 11 may contain particles formed by a non-conductive organic compound that does not contain the above-mentioned specific functional groups, may contain inorganic particles, and may also contain particles that are not buried in the silver-containing layer 2a. In addition, the contact materials 1 and 11 may also contain conductive particles, but the less the better, the short circuit of the contact caused by the shedding of the conductive particles can be suppressed, which is preferred. For example, preferably, more than 50% by volume of the particles contained in the contact materials 1 and 11 are non-conductive particles 2b, more preferably more than 60% by volume, more than 70% by volume, more than 80% by volume, more than 90% by volume, and further preferably all (100% by volume) are non-conductive particles 2b. In addition, the ratio of particles 2b at least partially buried in the silver-containing layer 2a to all particles contained in the contact materials 1 and 11 is preferably 50 area % or more in a cross section parallel to the film thickness direction of the silver-containing film 2, more preferably 60 area % or more, 70 area % or more, 80 area % or more, 90 area % or more, and even more preferably 100 area %.
[0077] The contact materials 1 and 11 of the embodiments of the present invention may also include other layers (e.g., a conductive substrate, a strike plating layer, etc.) on the basis of achieving the purpose of the present invention. For example, in the contact materials 1 and 11, the silver-containing film 2 may be formed on a conductive substrate (e.g., a substrate formed of copper or a copper alloy).
[0078] The contact material 1 according to the embodiment of the present invention is, for example, a contact material in which a predetermined amount of particles 2b are buried (eutectoidally deposited) in a silver-containing layer 2a by dispersing a predetermined amount of particles 2b in a silver (or silver alloy) plating solution, stirring and applying electricity, and performing a silver plating process on a substrate. In addition, depending on the circumstances, a primer silver plating process may be performed before performing the silver plating process.
[0079] In the process of electroplating by dispersing the particles 2 b in the plating solution, the following reactions (A) and (B) proceed simultaneously.
[0080] (A) The particles dispersed in the liquid are electrostatically or physically adsorbed (contacted) on the surface of the substrate.
[0081] (B) On the surface of the substrate, the silver-containing layer 2a undergoes a deposition (growth) reaction
[0082] "Eutectoid" occurs when the particles 2b adsorbed in (A) enter the silver-containing layer 2a of (B). Under conditions where the eutectoid plating is carried out stably, the particles 2b adsorbed at the beginning of the reaction enter the silver-containing layer 2a, and new particles 2b are adsorbed. Therefore, even when the plating process is stopped, the particles 2b are still visible from the outermost surface in most cases. In the usual eutectoid plating process, it is easy to manufacture a contact material 1 containing particles 2b partially buried in the silver-containing layer 2a and the rest exposed from the surface of the silver-containing layer 2a.
[0083] Here, the amount of the particles 2b co-precipitated in the silver-containing layer 2a (for example, the area ratio of the particles 2b) is determined by the balance between the adsorption frequency (A) and the plating film growth rate (B). Therefore, the amount of co-precipitation can be changed by changing the plating conditions such as the amount of particles 2b dispersed in the plating solution. For example, in the final stage of the plating treatment, a plating solution that does not contain the particles 2b dispersed in the plating solution is used for treatment, or the adsorption frequency (A) is reduced by changing the stirring speed of the plating solution, so as to provide a layer on the outermost surface of the plating that does not allow the particles 2b to co-precipitate, thereby manufacturing the contact material 11 in which the particles 2b are completely buried in the silver-containing layer 2a.
[0084] The contact materials 1 and 11 of the embodiments of the present invention not only have sufficient conductivity, but also have sufficient wear resistance (i.e., sufficiently low friction coefficient). Specifically, the contact materials 1 and 11 of the embodiments of the present invention can have an initial contact resistance of less than 0.5 mΩ, and can have a friction coefficient of less than 0.5 after 20 cycles of the sliding test described below.
[0085] <Sliding test>
[0086] After a hard Ag plating layer of 40 μm or more (Vickers hardness HV: 160 or more) is formed on a substrate, a dual material having a hemispherical protrusion with a curvature radius R = 1.8 mm is formed by a manual press, and the dual material is slid relative to the contact material 1 or 11 (containing the silver film 2) of the test object at a predetermined cycle with an applied vertical load of 3 N, a sliding distance of 10 mm, and a sliding speed of 80 mm / min. As a sliding test machine, for example, a horizontal load tester manufactured by Aikoh Engineering can be used.
[0087] In addition, the contact materials 1 and 11 of the embodiment of the present invention preferably have high heat resistance. Specifically, after heating at a specified temperature and time, the friction coefficient increase rate calculated by the following formula (2) is preferably less than 200%, and more preferably less than 120%. It is preferred that the above-mentioned friction coefficient increase rate is satisfied even if the heating temperature is high. The heating temperature is preferably above 140°C, more preferably above 160°C, and further preferably above 180°C. It is also preferred that the above-mentioned friction coefficient increase rate is satisfied even if the heating time is long. The heating time is preferably above 100 hours, more preferably above 200 hours, and further preferably above 500 hours.
[0088] Friction coefficient increase rate (%) = 100 × [friction coefficient after 500 cycles of the above sliding test after heating] / [friction coefficient after 500 cycles of the above sliding test without heating] ... (2)
[0089] Example
[0090] The embodiments of the present invention are not limited to the following embodiments, and may be appropriately modified within the scope of the above and below-mentioned purposes, and all of these are included in the technical scope of the embodiments of the present invention.
[0091] Example 1
[0092] A pure copper plate with a thickness of 0.3 mm was used as the plating substrate. After cleaning with acetone and degreasing the surface, a commercially available primer Ag plating solution (Dain Silver GPE-ST, manufactured by Yamato Chemical Industry Co., Ltd.) was used as the base for the plating treatment. A pure Ag plate was used as the counter electrode at 5 A / dm 2 A current density of 10000 was applied for 1 minute to apply a base Ag plating treatment with a thickness of about 0.1 μm, and the substrate was used as a substrate. Subsequently, a commercially available non-cyanide semi-gloss Ag plating solution (DainSilver GPE-SB manufactured by Yamato Chemical Co., Ltd.) was used to disperse various particles and surfactants shown in Table 1 in the plating solution, and the solution was stirred at 3 A / dm with a pure Ag plate as the counter electrode. 2 The current density was 0.040 for 5 minutes to obtain contact materials No. 1 to 9 including a silver-containing film in which each particle was coprecipitated (buried) in an Ag plating layer (silver content 99 mass % or more) with a thickness of about 10 μm. In addition, in No. 1 to 9, SURFLON S231 (manufactured by AGX SEIMI CHEMICAL) was used as a surfactant, and the amount added was 50 g / L.
[0093]
Table 1
[0094]
[0095] For the contact materials No. 1 to 9, the area ratio [A p / (A p +A Ag )×100(%)], (b) contact resistance and (c) wear resistance evaluation.
[0096] <(a) Area ratio of formula (1)[A p / (A p +A Ag )×100(%)]>
[0097] Using a scanning electron microscope (SEM, S-3500N manufactured by Hitachi, Ltd.), at an accelerating voltage of 20 kV and a working distance of 15 mm, cross-sectional SEM images (secondary electron images) parallel to the film thickness direction of the silver-containing film (and the silver-containing layer) were obtained for the samples of the contact materials No. 1 to 9 coated with a protective layer for cross-sectional SEM. The area A of the silver-containing layer Ag The area A of the bright part after binarization processing in the above manner using the image processing software "ImageJ" for the cross-sectional SEM image. In addition, in the cross-sectional SEM image, the average line of the concavities and convexities on the upper surface of the silver-containing layer is used as the boundary line between the silver-containing layer and the protective layer of the cross-sectional SEM sample. The area A of the part buried in the silver-containing layer among the plurality of particles is p , the dark part (corresponding to the part of the non-conductive organic compound) after the binarization process in the above manner is regarded as the area of the part buried in the silver-containing layer. Also, in the cross-sectional SEM image, the average line of the concavities and convexities on the upper surface of the silver-containing layer is regarded as the boundary line between the silver-containing layer and the protective layer of the cross-sectional SEM sample, and the part existing below the average line is regarded as the part buried in the silver-containing layer.
[0098] Figure 3A to Figure 3C An example of calculation of the area ratio of particles is shown in FIG. Figure 3A This is a cross-sectional SEM image of the contact material No. 2 parallel to the film thickness direction of the silver-containing film (and silver-containing layer). Figure 3B is from Figure 3A The image is obtained by cutting out only the silver-containing layer (and the particles buried in the silver-containing layer). Figure 3C yes Figure 3B The image is binarized. Figure 3C The area of the black part is divided by Figure 3B When the area is , the area rate is 2.51%.
[0099] <(b)Contact resistance evaluation>
[0100] For the silver-containing films of the contact materials No. 1 to 9, the contact resistance was measured using an electric contact simulator (manufactured by Yamazaki Seiki Laboratories). The applied load was 5 N, and the average value of the measurements at 3 locations was taken as the contact resistance of the contact materials No. 1 to 9. The contact resistance was 0.50 [mΩ] or less, and the conductivity was sufficient (0).
[0101] <(c) Evaluation of wear resistance>
[0102] After forming a hard Ag plating layer of about 50μm (Vickers hardness Hv: about 165) on a pure copper plate with a thickness of 0.25mm, a sample with a hemispherical protrusion with a curvature radius R = 1.8mm was formed by a manual press as a dual material. For the contact materials No. 1 to 9, a sliding test was performed using a sliding tester (Aikoh Engineering horizontal load tester) with an applied vertical load of 3N, a sliding distance of 10mm, and a sliding speed of 80mm / min. The sliding cycle was 20 cycles. The friction coefficient after sliding was 0.50 [mΩ] or less, which was considered sufficient (0) as wear resistance.
[0103] The above results are summarized in Table 2. In the column "Preventing short circuit", when 50% by volume or more of the particles contained in the contact material are non-conductive particles, the short circuit of the contact caused by the falling of particles can be fully suppressed, which is (0). In addition, the values marked with * indicate that they are out of the scope of the embodiments of the present invention.
[0104]
Table 2
[0105]
[0106] The following observations can be made from the results of Table 2: All of the contact materials Nos. 2 to 4 and 6 to 9 satisfy the requirements specified in the embodiment of the present invention, can sufficiently suppress short circuits of contacts due to the falling of conductive particles, and have sufficient wear resistance and conductivity.
[0107] On the other hand, the contact materials No. 1 and 5 in Table 2 do not satisfy the requirement specified in the embodiment of the present invention, that is, the area ratio range (0.50 to 12.10) of formula (1), and are insufficient in wear resistance or conductivity.
[0108] Example 2
[0109] The contact materials No. 10 to 12 were obtained by changing the buried particle types and addition amounts from Example 1 to those shown in Table 3. In addition, No. 10 to 12, SURFLON S231 (manufactured by AGX SEIMI CHEMICAL) was used as a surfactant, and the addition amount was 50 g / L in No. 10 and 10 g / L in No. 11 and 12.
[0110]
Table 3
[0111]
[0112] For the contact materials No. 10 to 12, (d) thermogravimetric differential thermal analysis (TG-DTA) and (e) heat resistance evaluation were performed.
[0113] <(d)Thermogravimetric differential thermal analysis (TG-DTA)>
[0114] The organic compound particles used for contact materials No. 10 to No. 12 were subjected to thermogravimetric differential thermal analysis using a differential thermal balance (Thermo plus EVOII, manufactured by Rigaku Corporation) at a heating rate of 10°C / min from room temperature to a maximum of 1000°C in the atmosphere to determine the melting point, decomposition point and combustion point of each compound particle.
[0115] <(e) Heat resistance evaluation>
[0116] The contact materials No. 10 to No. 12 were placed in a thermostat (DN-43, manufactured by Yamato Scientific) set at 140 to 180°C in an atmospheric environment, heated for 100 to 500 hours, and then subjected to the sliding test in the above-mentioned (c) wear resistance evaluation. The sliding cycle was 500 cycles. Figures 4 to 6 , the heat resistance evaluation results of contact materials No. 10 to 12 are shown respectively.
[0117] The above results are summarized in Table 4. In the column "TG-DTA results", "-" means that the corresponding temperature is not shown. In the column "Heat resistance evaluation results", the increase rate of the friction coefficient calculated by the above formula (2) after heating for 500 hours at each temperature is 120% or less, which is particularly good (◎), and 200% or less, which is good (○), and other than that, it is ×. In addition, "-" in the column "Heat resistance evaluation results" means that no evaluation was performed.
[0118]
Table 4
[0119]
[0120] According to the results in Table 4, there is a correlation between the melting point of the non-conductive organic compound and the heat resistance evaluation result. The contact materials No. 11 and 12 having a melting point of 140° C. or above or showing no melting point have good heat resistance.
[0121] [Reference example]
[0122] The following describes, using reference examples, the requirements of the embodiment of the present invention, that is, "a non-conductive organic compound comprising, in a unit molecular structure, a fluorine group (-F), a methyl group (-CH3), a carbonyl group (-C(=O)-), an amino group (-NR 1 R 2 , where R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2 The good effect of "any one or more selected from the group consisting of the group consisting of the hydroxyl group (-OH), the ether bond (-O-) and the ester bond (-C(=O)-O-)" is achieved.
[0123] [Reference Example 1]
[0124] A pure copper plate with a thickness of 0.3 mm was used as the plating substrate. After the surface was degreased by acetone cleaning, it was used as the base for plating treatment. A commercially available primer Ag plating solution (Dain Silver GPE-ST, manufactured by Yamato Chemical Industry Co., Ltd.) was used as the base. A pure Ag plate was used as the counter electrode at 5 A / dm 2 A current density of 10000 was applied for 1 minute to apply a base Ag plating treatment with a thickness of about 0.1 μm, and the substrate was used as a substrate. Afterwards, a commercially available non-cyanide semi-gloss Ag plating solution (Dain Silver GPE-SB manufactured by Yamato Chemical Co., Ltd.) was used, and a pure Ag plate was used as a counter electrode at 3 A / dm 2 The current density was 0.20 for 5 minutes to form a semi-glossy Ag coating (containing 99% by mass or more) with a thickness of about 10 μm. Then, a liquid containing various particles (or dispersions of particles) shown in Table 5 suspended in alcohol at a ratio of 20 mg / ml was dripped onto the surface of the Ag coating at a rate of 0.2 ml / cm 2 and dried to produce contact materials No. 13 to No. 24, which include a silver-containing film in which various particles are in contact with the surface of the Ag-plated layer.
[0125]
Table 5
[0126]
[0127] For the contact materials No. 13 to No. 24, (f1) wear resistance evaluation was performed.
[0128] <(f1)Abrasion resistance evaluation>
[0129] The sliding test in the wear resistance evaluation (c) of the above Example 1 was carried out. The number of sliding cycles was a maximum of 500 cycles. The results are shown in Figure 7 to Figure 18 middle. Figure 7 to Figure 18 These are the results of sliding tests on the contact materials of Test Nos. 13 to 24, respectively.
[0130] The maximum value of the friction coefficient (ratio of horizontal load to vertical load) in each sliding cycle is measured. If the friction coefficient after 500 cycles is higher than 0.50, it is considered insufficient (×), if the friction coefficient after 500 cycles is less than 0.50, it is slightly insufficient (△), if the friction coefficient after 300 cycles is less than 0.50, it is sufficient (○), and if the friction coefficient after 100 cycles is less than 0.30, it is good (◎). In addition, for multiple measurements, the average value is used for judgment.
[0131] The above results are summarized in Table 6. In the "Prevention of Short Circuit" column, when 50% by volume or more of the particles contained in the contact material are non-conductive particles, the short circuit of the contact caused by the shedding of particles can be fully suppressed, which is (○), and when less than 50% by volume of the particles contained in the contact material are non-conductive particles (that is, when more than 50% by volume of the particles contained in the contact material are conductive particles), there is a possibility that the short circuit of the contact may be caused by the shedding of particles (×).
[0132]
Table 6
[0133]
[0134] The results of Table 6 allow the following investigation. The contact materials No. 13 to 18 in Table 6 are all non-conductive organic compounds, and contain at least one selected from the group consisting of fluorine, methyl, carbonyl, amino, hydroxyl, ether bond (-O-) and ester bond (-C(=O)-O-) in the unit molecular structure, so the friction coefficient after 300 cycles is less than 0.50. In addition, since the contact materials No. 13 to 16 in Table 6 meet the preferred requirements of non-conductive organic compounds and contain at least one selected from the group consisting of carbonyl, amino and hydroxyl groups in the unit molecular structure, the friction coefficient after 100 cycles is less than 0.30, which is a preferred result.
[0135] [Reference Example 2]
[0136] A pure copper plate with a thickness of 0.3 mm was used as the plating substrate. After cleaning with acetone and degreasing the surface, a commercially available primer Ag plating solution (Dain Silver GPE-ST, manufactured by Yamato Chemical Industry Co., Ltd.) was used as the base for the plating treatment. A pure Ag plate was used as the counter electrode at 5 A / dm 2 A current density of 10000 was applied for 1 minute to apply a base Ag plating treatment with a thickness of about 0.1 μm, and the substrate was used as a substrate. Afterwards, a commercially available non-cyanide semi-gloss Ag plating solution (DainSilver GPE-SB manufactured by Yamato Chemical Co., Ltd.) was used, and a pure Ag plate was used as a counter electrode at 3 A / dm 2The current density was 0.20 for 5 minutes to form a semi-glossy Ag coating (containing 99% by mass or more) with a thickness of about 10 μm. Then, a liquid containing various particles (or dispersions of particles) shown in Table 7 suspended in alcohol at a ratio of 20 mg / ml was dripped onto the surface of the Ag coating at a rate of 0.2 ml / cm 2 and dried to produce contact materials No. 25 to No. 28, which include a silver-containing film in which various particles are in contact with the surface of the Ag-plated layer.
[0137]
Table 7
[0138]
[0139] For the contact materials No. 25 to No. 28, (f2) wear resistance evaluation was performed.
[0140] <(f2)Abrasion resistance evaluation>
[0141] Using a ball-on-disc friction and wear tester (CSM, Tribometer), a φ6mm high carbon chromium bearing steel (SUJ2) ball was used as the counter material, and 100 cycles of reciprocating sliding tests were performed on contact materials No. 25 to 28. The vertical load applied was 1N, the sliding width (sliding stroke) per cycle was 10mm, and the average sliding speed was 30mm / second.
[0142] The results are shown in Figure 19 to Figure 22 middle. Figure 19 to Figure 22 , respectively, are the results of the above-mentioned wear resistance evaluation conducted on the contact materials of Test Nos. 25 to 28.
[0143] The maximum value of the friction coefficient (ratio of horizontal load to vertical load) in each sliding cycle was measured. If the friction coefficient after 100 cycles was higher than 1.0, it was considered insufficient (×), if the friction coefficient after 100 cycles was between 0.20 and 1.0, it was considered sufficient (○), and if the friction coefficient after 100 cycles was lower than 0.20, it was considered good (◎). In addition, for multiple measurements, the average value was used for judgment.
[0144] The above results are summarized in Table 8. In the "Prevention of Short Circuit" column, when 50% by volume or more of the particles included in the contact material are non-conductive particles, the short circuit of the contact caused by the falling of particles can be fully suppressed, which is (○), and when less than 50% by volume of the particles included in the contact material are non-conductive particles (that is, when more than 50% by volume of the particles included in the contact material are conductive particles), there is a possibility that the short circuit of the contact may be caused by the falling of particles (×).
[0145]
Table 8
[0146]
[0147] According to the results of Table 8, the following investigation can be conducted. The contact materials No. 25 to 27 in Table 8 are all non-conductive organic compounds, and contain any one or more selected from the group consisting of fluorine, methyl, carbonyl, amino, hydroxyl, ether bond (-O-) and ester bond (-C (=O)-O-) in the unit molecular structure, so the friction coefficient after 100 cycles is less than 1.0. In addition, the contact material No. 27 in Table 8 meets the preferred requirements of non-conductive organic compounds, and contains any one or more selected from the group consisting of carbonyl, amino and hydroxyl groups in the unit molecular structure, so the friction coefficient after 100 cycles is less than 0.20, which is a preferred result.
[0148] The present application claims priority based on Japanese Patent Application No. 2022-107713 filed on July 4, 2022 and Japanese Patent Application No. 2022-153957 filed on September 27, 2022. Japanese Patent Application No. 2022-107713 and Japanese Patent Application No. 2022-153957 are incorporated herein by reference.
[0149] Description of Reference Numerals
[0150] 1 Contact material
[0151] 2 Silver film
[0152] 2a Silver-containing layer
[0153] 2b Particles formed from non-conductive organic compounds
[0154] 11 Contact material
Claims
1. A contact material comprising a silver-containing film, wherein: The silver-containing film comprises: a silver-containing layer containing 50% by mass or more of silver; a plurality of particles formed of a non-conductive organic compound, at least a portion of each particle being buried in the silver-containing layer, The non-conductive organic compound comprises, in a unit molecular structure, fluorine group -F, methyl group -CH3, carbonyl group -C(=O)-, amino group -NR 1 R 2 , hydroxyl group -OH, ether bond -O- and ester bond -C(=O)-O-, wherein -NR 1 R 2 In, R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2 Can be the same or different, And satisfy the following formula (1), 0.50≤A p / (A p +A Ag )×100≤12.10 …(1) In formula (1), A p A is the area of the portion of the plurality of particles formed of the non-conductive organic compound buried in the silver-containing layer in a cross section parallel to the film thickness direction of the silver-containing film, Ag It is the area of the silver-containing layer in a cross section parallel to the film thickness direction of the silver-containing film.
2. The contact material according to claim 1, wherein: When the non-conductive organic compound is subjected to thermogravimetric differential thermal analysis at a temperature increase rate of 10° C. / min from room temperature to a maximum of 1000° C., the melting point is 140° C. or higher, or no melting point is shown.
3. The contact material according to claim 1, wherein: When the non-conductive organic compound is subjected to thermogravimetric differential thermal analysis at a heating rate of 10°C / min from room temperature to a maximum of 1000°C, if a decomposition point is shown, the decomposition point is 500°C or less, and if a melting point is shown instead of a decomposition point, the melting point is 500°C or less.
4. The contact material according to claim 2, wherein: When the non-conductive organic compound is subjected to thermogravimetric differential thermal analysis at a heating rate of 10°C / min from room temperature to a maximum of 1000°C, if a decomposition point is shown, the decomposition point is 500°C or less, and if a melting point is shown instead of a decomposition point, the melting point is 500°C or less.
5. The contact material according to any one of claims 1 to 4, wherein The non-conductive organic compound comprises carbonyl -C(=O)-, amino -NR 1 R 2 Any one or more selected from the group consisting of -NR 1 R 2 In, R 1 and R 2 is hydrogen or a hydrocarbon group, R 1 and R 2 Can be the same or different.
Citation Information
Patent Citations
gaming machines
JP2022107713A
Semiconductor pressure sensor and pressure sensor device
JP2022153957A